Methodological study on simultaneous detection of 6 tumor invasion and metastasis markers including MMP-9 by microfluidic chip-based magnetic particle immunofluorescence assay - Junhao Li; Yiran Wang (PLoS ONE, 2026)
Objective Conventional tumor marker detection technologies are confined to single-index sequential testing, with drawbacks like prolonged turnaround times, high sample consumption, and heavy reliance on large precision instruments. They fail to meet the needs of clinical scenarios such as point-of-care testing (POCT), primary medical institution screening, and emergency rapid assessment. This study aims to develop a multi-index simultaneous quantitative detection system, providing an efficient, convenient, and reliable technical solution for early accurate diagnosis and whole-course dynamic monitoring of tumors. Methods Leveraging the core advantages of micro fluidic chips—miniaturization, integration, and low reagent consumption—a detection platform was designed to simultaneously quantify six tumor-associated markers: matrix metalloproteinase 9 (MMP-9), vascular endothelial growth factor A (VEGF-A), soluble neural cadherin (sN-cadherin), osteoprotegerin (OPG), lysyl oxidase (LOX), and angiopoietin 2 (ANG-2). Methodological characterization included linear range verification, limit of detection (LOD) determination, precision evaluation, and specificity tests (cross-reactivity, matrix interference, and background interference). Consistency with clinical gold-standard methods was assessed via correlation analysis, Kappa test, and Bland-Altman analysis. Diagnostic efficacy was evaluated using ROC curve analysis, and detection timeliness was improved by optimizing the “two-reaction and two-washing” core process. Results All six markers exhibited excellent analytical performance: the coefficients of determination (R²) of their dose-response curves ranged from 0.9968 to 0.9993, with linear ranges of 0.012–16,000 pg/mL (VEGF-A, OPG, ANG-2) and 0.016–9,600 ng/mL (MMP-9, sN-cadherin, LOX), and limits of detection (LODs) of 0.012–0.019 pg/mL (or equivalent ng/mL units). Precision was outstanding: intra-batch relative standard deviations (RSDs) were 2.51%–5.12% for low-concentration samples and 0.88%–4.14% for high-concentration samples, while inter-batch RSDs, chip repeatability RSDs, and storage stability RSDs were all ≤ 6.76%, meeting the clinical threshold standard of ≤10%. Specificity verification showed that both cross-reactivity rates and interference rates were significant non-specific binding or matrix interference observed. Compared with the gold standard, the coefficient of determination (R²) was > 0.95, the Kappa coefficient was 0.8–1.0 (excellent agreement), and over 90% of sample deviations fell within the 95% confidence interval (CI). The area under the receiver operating characteristic curve (AUC) ranged from 0.9546 to 0.9882, with both detection sensitivity and specificity reaching 93%–98%. The detection system shortened the total detection time to 24 minutes, required only microliter-scale sample consumption, and was 5–8 times faster than enzyme-linked immunosorbent assay (ELISA)/chemiluminescence immunoassay. Conclusion The microfluidic chip system integrates high sensitivity, precision, specificity, rapidity, and miniaturization, achieving high equivalence with traditional methods. It breaks through conventional limitations, meeting clinical needs for early screening, dynamic monitoring, and large-scale surveillance, with significant clinical transformation and industrialization prospects. Future optimization will involve multi-center validation, panel expansion, and AI integration to support personalized tumor care.